Experimental and Numerical Analysis of Hollow and Solid Reinforced Concrete Piers under Static and Impact Loadings - Pengfei Yao; Junyu Zhu; Lu Zhu; Hai Fang; Changgen Qian (Shock and Vibration)
Collision on reinforced concrete (RC) piers by moving vessels or vehicles is a significant issue. This paper presents the static and impact behavior of RC piers with different hollow ratios. Three specimens were statically tested to obtain the load-displacement response. Low-velocity collision on eleven RC piers was conducted under the same velocity of 2.42 m/s. The damage process, failure mode, and force response were comprehensively analyzed. The experimental results indicate that the hollow ratio plays a significant role in the failure mode and ultimate load of RC piers under static and impact loadings. For RC piers with a hollow ratio of 0 and 0.4, the global failure dominated the damage process. However, failure of piers with a hollow ratio of 0.6 was governed by the local damage near the loading point. The static load capacities of the RC piers with a hollow ratio of 0.4 and 0.6 were 1.27% and 60.5% smaller than that of the solid pier, respectively. RC piers with a higher hollow ratio or lighter drop weight suffer smaller peak impact force. The increase of the longitudinal reinforcements leads to a promotion of the peak and mean impact force. Furthermore, the numerically predicted failure modes and impact load response show satisfactory agreement with the experimental results.